Profil Darah Domba Lepas Sapih yang Diberi Konsentrat Berbasis Protein Nabati atau Hewani: Blood Profile of Weaned Lambs Fed Concentrates Containing Plant- or Animal-Derived Protein - Fassah, Dilla Mareistia; Janah, Fatiah Finanur; Rangkuti, Farhan Ananda; Diapari, Didid; Tarigan, Andi; Astuti, Dewi Apri (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2025)
This study aimed to evaluate starter concentrate containing plant-derived protein (Indigofera sp.) or animal-derived protein (Black soldier fly (BSF) larvae meal), on hematological and blood metabolite profiles of weaned Dorper lambs. A total of 21 weaned Dorper male lambs were utilized in a Completely Randomized Design (CRD) with 3 treatment groups and seven replications. The treatment groups included P0 = Martabe Farm feed (control), P1 = forage and starter concentrate containing Indigofera sp., and P2 = forage and starter concentrate containing BSF larvae meal. The parameters measured were nutrient intake, amino acid intake, hematology, and blood metabolites. The concentrate starter containing Indigofera sp. or BSF larvae meal significantly increased (p<0.05) nutrients and most of the individual amino acid intake, BUN, and erythrocyte count. It is concluded that the use of plant-based protein (Indigofera sp.) or animal-based protein (BSF larvae meal) in starter concentrate enhances nutrient intake and does not interfere with blood homeostasis in weaned Dorper male lambs. Key words: black soldier fly larvae meal, blood metabolites, hematology, Indigofera sp., weaned lamb